Decay estimates for three-dimensional Navier–Stokes equations with damping. (August 2021) - Zhao, Xiaopeng
Abstract: In this paper, the optimal decay rates of solutions for three-dimensional incompressible Navier–Stokes equations with damping term u β − 1 u are established. Bounds on the H . − s negative Sobolev norms is shown to be preserved along time evolution and enhance the decay rates.